Perceptions of Adults Adopted as Children: Implications for Family Counselors. (October 2016) - Duemer, Lee; Hicks, Janet Froeschle; Brendle, Janna
This qualitative phenomenological study investigated the experiences of adults adopted as children. Individual and follow-up interviews were conducted with four participants. We identified six primary themes related to family experience and a better understanding of adopted children, adults as well as special issues that might be considered in family counseling. Implications for counselors are discussed in this article.